Strategy for Implementing the Tiatiki Concept in Conservation Resource - Amida Laurita Snahan; Basa T. Rumahorbo; Yanviter Manalu; Maklon Warpur; Johnson Sialagan (Jurnal Penelitian Pendidikan IPA, 2024)
Strategy is a plan that is intended to achieve the desired goal, or in other words, Strategy is a long-term plan that is prepared to lead to the achievement of certain goals and targets, while the Coastal area is a transition area between land and sea ecosystems which is influenced by changes on land and sea. Research on strategies for implementing the Tiatiki concept in coastal resource conservation in Tabla Supa Depapre village, Jayapura Regency was carried out in August-October 2023 using survey and interview methods. Next, data analysis can be carried out using SWOT analysis. The results of data analysis show that there are 5 strategies for conserving coastal resources in Tabla Supa Village, Depapre District, Jayapura Regency: Developing tourism by involving the community and local wisdom, Increasing community capacity in managing coastal and marine resources in a sustainable manner based on local wisdom, Utilizing local wisdom through the Tabla Supa village community institution in minimizing the negative impacts of using coastal resources that are not environmentally friendly, managing coastal area resources with an integrated system based on community-based management and involving the community and increasing community understanding, especially the younger generation, about the values of local wisdom including Tiatiki by Village community organizations.